Agriculture and Water Availability Show Contrasting Effects on Bats in a Mediterranean Island of Outstanding Chiropteran Biogeographical Value - Luca Cistrone; Ana Margarida Augusto; Gaetano Fichera; Hugo Rebelo; Danilo Russo (Ecology and Evolution)
ABSTRACT With their unique ecosystems and evolutionary dynamics, small islands offer fascinating contexts to explore animal diversity. Island bats are key players in maintaining ecological balance. However, their populations are threatened worldwide, necessitating comprehensive research and conservation strategies. Pantelleria, a small Mediterranean island and a biogeographic crossroad between Europe and Africa, offers an excellent model to exemplify the challenges to bat conservation in such geographic contexts. We tested three hypotheses: (1) bats would show weak preference patterns for landscape composition due to the island's heterogeneous landscapes, (2) farmland (especially vineyards) would strongly affect bat activity, and (3) distance from water sources would highly influence bat richness and activity. We surveyed bats acoustically using Audiomoth recorders covering most of the island's surface. We recorded seven bat species, including endangered Plecotus gaisleri, Myotis punicus and Rhinolophus mehelyi. Bats showed weak preferences for specific landscape composition, but the dominant species (Pipistrellus kuhlii) decreased its activity for increasing portions of vineyards within the landscape. Moreover, distance to water critically influenced bat richness and activity. Agricultural expansion, pesticide use and human activities pose significant threats to bats on Pantelleria. We advocate for sustainable farming practices and careful water resource management to safeguard bat habitats and mitigate these threats. Conservation should target vineyards, a key economic resource to produce world‐renowned wine ‘Passito di Pantelleria’ by reducing pesticide use and adopting organic management. Water might be supplemented in critical dry habitats. We urge the preservation of bat diversity to support ecosystem health and resilience on small islands like Pantelleria.